Beban Kerja dan Motivasi terhadap Kinerja Pegawai pada PT. PLN (Persero) UID Riau dan Kepulauan Riau UP3 Tanjungpinang - Kyara Clarissa; Ratri Wahyuningtyas (IPM2KPE, 2024)
The aim of this research is to identify factors that influence the workload and work motivation of employees at PT. PLN (Persero) UID Riau and Riau Islands UP3 Tanjungpinang. This research uses a questionnaire as a primary data collection instrument with a quantitative research approach. The research population is employees of PT. PLN (Persero) UID Riau and UP3 Riau Tanjungpinang Islands, and the entire population was sampled, with a total of 199 workers, using a saturated sampling approach. Descriptive analysis, validity testing, reliability testing, and hypothesis testing were carried out using Structural Equation Modeling (SEM-PLS) with Smartpls 3. The results showed that workload had an influence but was not significant on employee performance, while motivation had a significant influence on employee performance. . In conclusion, it is hoped that it can provide input for PT. PLN (Persero) UID Riau and Riau Islands UP3 Tanjungpinang in improving human resources, especially in terms of workload, motivation and employee performance. Keywords: Workload, Employee Performance, Motivation